2005
DOI: 10.1002/art.21580
|View full text |Cite
|
Sign up to set email alerts
|

Use of self‐management behaviors to cope with rheumatoid arthritis stressors

Abstract: Objective. To examine self-management behaviors used to cope with 5 rheumatoid arthritis (RA)-related stressors (pain, fatigue, physical limitations, joint changes, and symptom unpredictability) and the relationship between use of selfmanagement behaviors and ability to perform life activities. Methods. Data were from telephone interviews of 511 persons with RA. Participants were presented with lists of self-management behaviors for each stressor and asked to indicate which they had used in the past year. Perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
33
2
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 47 publications
7
33
2
5
Order By: Relevance
“…A qualitative study found that women affected by rheumatoid arthritis (within a sample aged 30-80 years old) emphasized the importance of maintaining a sense of control, through, for example, finding ways of maintaining their valued activities (McPherson, Brander, Taylor, & McNaughton, 2001). Helplessness, a willingness to accommodate to arthritis, and passive coping strategies such as resting and inactivity, seem to be associated with increased levels of depression, more functional restrictions, loss of activities, and higher levels of pain (Axford, Heron, Ross, & Victor, 2008;Katz, 2005;Ramjeet, Smith, & Adams, 2008). People with this condition who have positive attitudes and strategies (such as optimism, a willingness to re-prioritize and reframe their situation), and social support, are more likely to maintain their activity repertoires (Katz, 2005;Sinclair & Blackburn, 2008;Treharne, Kitas, Lyons & Booth, 2005;Treharne, Lyons, Booth & Kitas, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A qualitative study found that women affected by rheumatoid arthritis (within a sample aged 30-80 years old) emphasized the importance of maintaining a sense of control, through, for example, finding ways of maintaining their valued activities (McPherson, Brander, Taylor, & McNaughton, 2001). Helplessness, a willingness to accommodate to arthritis, and passive coping strategies such as resting and inactivity, seem to be associated with increased levels of depression, more functional restrictions, loss of activities, and higher levels of pain (Axford, Heron, Ross, & Victor, 2008;Katz, 2005;Ramjeet, Smith, & Adams, 2008). People with this condition who have positive attitudes and strategies (such as optimism, a willingness to re-prioritize and reframe their situation), and social support, are more likely to maintain their activity repertoires (Katz, 2005;Sinclair & Blackburn, 2008;Treharne, Kitas, Lyons & Booth, 2005;Treharne, Lyons, Booth & Kitas, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Use of other behavioral accommodations, such as limiting activities or taking more time to perform them, to improve functioning or reduce disability may be more common than use of devices or assistance (5)(6)(7)(8). In a study of self-management behaviors used to cope with the functional limitations of rheumatoid arthritis (RA), taking more time to perform activities was the most common strategy reported (by 80% of respondents), followed closely by avoiding or limiting certain activities (75% of respondents) (7).…”
Section: Introductionmentioning
confidence: 99%
“…In a study of self-management behaviors used to cope with the functional limitations of rheumatoid arthritis (RA), taking more time to perform activities was the most common strategy reported (by 80% of respondents), followed closely by avoiding or limiting certain activities (75% of respondents) (7). Asking for help was reported by ϳ60%, but use of equipment was mentioned only rarely.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in the European Research on Incapacitating Diseases and Social Support cohort of patients with early RA it was demonstrated that patients with a greater amount of specific social support or a stronger specific support network experienced less functional limitation and less psychological distress (Demange et al, 2004). Controlled studies of RA patients demonstrated that the ability of self-management behaviours (accommodation, active remediation, perseverance) can decrease impact of RA-related stressors (pain, fatigue, physical limitations, joint changes, and symptom unpredictability) to perform life activities (p < 0.01 -0.0001) (Katz et al, 2005).…”
Section: Wwwintechopencommentioning
confidence: 99%